On the types of Bolboceratidae (Coleoptera: Scarabaeoidea) in the Swedish Museum of Natural History in Stockholm - Rossini, Michele; Forshage, Mattias (Zootaxa, 2023)
The investigation of the Bolboceratidae collection of the Stockholm Museum of Natural History (NHRS) yielded 12 type specimens of eight Afrotropical and one Australian species. The majority of these types belongs to species described by Carl Henrik Boheman (1796–1868) based on specimens collected by Johan August Wahlberg (1810–1856) in southern Africa. In two of these species, we found ambiguity among potential syntypes. Therefore, based on comparison with original descriptions, we designate lectotypes for Bolboceras caffrum Boheman, 1857 and Bolboceras exasperans Péringuey, 1908, both of which are today classified in the genus Bolbocaffer Vulcano, Martínez & Pereira, 1969. Finally, we establish Bolboceras matabele Péringuey, 1908 (syn. nov.) as a junior subjective synonym of B. exasperans, we confirm a few synonymies that were historically established without study of type specimens, and we resurrect Bolboceras dorsuale Boheman, 1857 from previous synonymy under B. maculicolle Boheman, 1857 (Mimobolbus dorsualis (Boheman, 1857) n. comb. and stat. rev.).